2018
DOI: 10.14419/ijet.v7i4.35.23103
|View full text |Cite
|
Sign up to set email alerts
|

Flood and Flash Flood Geo-Hazards in Malaysia

Abstract: Floods are natural phenomena of geo-hazards that usually happened when experiencing prolonged heavy rainfalls. Floods in Malaysia can be categorized into monsoon floods and flash floods. Monsoon floods is caused of Northeast Monsoon season commences in early November and ends in March that brings heavy rainfall, particularly to the east coast states of Peninsular Malaysia and western Sarawak. Flash floods usually occur in areas with rapid development by a rapid rise in water level, high velocity, and large amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…In the coming decades, climate change is expected to make the situation even more difficult. 1886, 1926, 1931, 1947, 1954, 1957, 1965, 1967, 1970/1971, 1988, 1993, 1996(Buslima et al 2018.…”
Section: Floodmentioning
confidence: 99%
See 2 more Smart Citations
“…In the coming decades, climate change is expected to make the situation even more difficult. 1886, 1926, 1931, 1947, 1954, 1957, 1965, 1967, 1970/1971, 1988, 1993, 1996(Buslima et al 2018.…”
Section: Floodmentioning
confidence: 99%
“…The annual occurrence of the flood hazard has compelled oil palm growers to plan ahead of time in order to minimise its impacts (Safiah Yusmah et al 2020 ). Large floods with devastating impacts that occurred in Malaysia include 1886, 1926, 1931, 1947, 1954, 1957, 1965, 1967, 1970/1971, 1988, 1993, 1996, 2000, 2006/2007, 2008, 2009, and 2010 (Buslima et al 2018 ).…”
Section: Climate Change and Extreme Weather Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from a study showed that farmers can also be severely affected by floods with a limited capacity to cope and adapt (Brida et al, 2013). In the case of Malaysia, the flash flood of December 2014 can be classified as one of the worst floods with a massive impact on people, properties, agriculture, livestock, and infrastructure facilities (Buslima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The accurate prediction of a river water level improves flood prediction systems and can act as a warning alarm for early decision-making and planning to reduce the effect of flood events which is considered as one of the most damaging natural hazards on life and property (Hettiarachchi & Thilakumara, 2014;Morales-Pinzón et al, 2015;Tsujikura et al, 2016;Xu et al, 2019). In Malaysia, floods and flash floods are often happened due to prolonged heavy rainfall; however, the possibility of floods may increase as a result of climate change and global warming (Arbain & Wibowo, 2012;Buslima et al, 2018;Suri et al, 2014). To deal with the flood phenomena, three categories of critical river water levels have been introduced by the Department of Irrigation and Drainage CONTACT Saad Sh.…”
Section: Introductionmentioning
confidence: 99%